2021
DOI: 10.11646/zootaxa.4966.2.1
|View full text |Cite
|
Sign up to set email alerts
|

A checklist of Scoliidae (Insecta: Hymenoptera) from China

Abstract: A checklist of all confirmed species of the family Scoliidae (Hymenoptera) from China is made based on the Chinese specimens in the Naturalis Biodiversity Center (RMNH, Leiden) and on additional specimens from the Chinese Academy of Insect Science (IOZ, Beijing), the Zhejiang University (ZJUH, Hangzhou), and the Sun Yat-sen University (SYSUBM, Guangzhou). The Scoliid species from China belong to one subfamily, two tribes, 11 genera and 52 species. Two species are deleted from the fauna of China: Campsomeriella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 785 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Of the four genera within Campsomerini, the generic status seems to be supported by the phylogenetic analysis of the COI sequences, as the branches representing each genus are clearly separated from each other (Figure 1). Genera Phalerimeris Betrem, Micromeriella Betrem, and Sericocampsomeris Betrem previously were all elevated from subgenera of Campsomeris [18]. In this study, these genera are all represented by one species but with multiple specimens collected from various localities and form their own clusters that are clearly separated from each other on the ML tree.…”
Section: Tribe Campsomerinimentioning
confidence: 51%
See 4 more Smart Citations
“…Of the four genera within Campsomerini, the generic status seems to be supported by the phylogenetic analysis of the COI sequences, as the branches representing each genus are clearly separated from each other (Figure 1). Genera Phalerimeris Betrem, Micromeriella Betrem, and Sericocampsomeris Betrem previously were all elevated from subgenera of Campsomeris [18]. In this study, these genera are all represented by one species but with multiple specimens collected from various localities and form their own clusters that are clearly separated from each other on the ML tree.…”
Section: Tribe Campsomerinimentioning
confidence: 51%
“…Studies have found that COI has a low signal for phylogenetic analysis above the genus level [31]. Morphologically, the interrelationships within Scoliini are also unclear, for example, genera such as Carinoscolia, Megascolia and Liacos share many similarities and were treated as subgenera of Scolia in the past [18]. However, each species (some are represented by multiple specimens) recovered on the tree are clearly separated from all neighboring species and are identical to the number of species identified based on morphological characters, suggesting that the species in question can be identified unambiguously by DNA barcoding.…”
Section: Tribe Scoliinimentioning
confidence: 99%
See 3 more Smart Citations